Exposição simultânea ao vinilciclohexeno e ao metilmercúrio em Drosophila melanogaster: análise bioquímica e molecular - Piccoli, Bruna Candia (2017)
Exposition to toxic compounds is becoming more frequent. This fact is of relevant since xenobiotics cause an imbalance in the body homeostasis mainly inducing oxidative stress. In addition, they can alter enzyme activities and gene expression, especially of those related to the antioxidant system and the inflammatory response, which can be used as an indicator of toxicity. Among these compounds vinylcyclohexene (VCH), a byproduct of plastic and derivatives production, and methylmercury (MeHg), mainly found in fish, stand out. We are constantly exposed to a wide range of xenobiotics and it is necessary to study the effects of exposure to toxic agents concomitantly. Thus, this work aims to study the isolated and interactive effects of MeHg and VCH on the oxidative stress and gene modulation in Drosophila melanogaster, since these have similarities in their mechanisms of toxicity. We used different concentrations of MeHg (0 a 400 μM) and VCH (0 a 10 mM) to make survival curves. The highest concentrations of the compounds that did not alter fly survival were used in the interactive effect study. Reactive species production and glutathione S-transferase (GST) and acetylcholinesterase (AChE) enzymes activities were evaluated in the head and in the body of the flies one and three days after individual and concomitant exposure to VCH and MeHg. Changes in gene expression related to redox state and inflammatory cell responses were evaluated after three days of exposure in both tissues. There was a decrease in reactive species production after one day of exposure to MeHg in the head of the flies, in contrast, all treatments increased the reactive species production in the body of the flies after one day of exposure and only the coexposition of the compounds induced an increase in this parameter after three days. Regarding to GST, after one day of exposure to VCH there was an increased the activity of this enzyme whereas exposure to MeHg induced this increased after three days of exposure in the head of the flies. In the body, all treatments increased GST activity after one day of exposure to compounds and after three days, only exposure to MeHg increased the activity of this enzyme. The treatments did not alter AChE activity in the head of the flies. There was an increase in Relish gene expression after the exposure to MeHg in the body of the flies. Therefore, the exposure to VCH and MeHg induced oxidative stress and activation of the inflammatory response. We emphasize that biochemical and molecular tests were able to detect changes even when the mortality rate of the flies was not affected. In most tests we failed to detect an increase in toxic effects after co-exposure, which may be due to the fact that the two compounds tested, despite similarities in the mechanisms of toxicity, have different toxicity targets.